Differences in EMG of Trunk and Lower Limb According to Attack Method and Phase During Volleyball - Jeong, H. J.; Baek, G. E.; Kim, K. H. (International Journal of Internet, Broadcasting and Communication, 2021)
The purpose of our study is to confirm the trend of the muscle activity of the trunk and lower limb muscles by the attack method and phase during volleyball exercise. To achieve this purpose, spike serve and spike were conducted for 9 male middle school students, and at that time, it was divided into four phase, such as run jump, take off, impact, and follow, and the rectus abdominis, erector spine, and left rectus femoris, left biceps femoris, left anterior tibialis, left gastrocnemius midialis, right rectus femoris, right biceps femoris, right anterior tibialis, right gastrocnemius midialis, were examined. Spike serve and spike were each performed three times, and randomly cross-allocated to extract accurate data. We was no difference in all muscles according to the attack method, and the muscle activity of the rectus abdominis was highest in the impact phase and the muscle activity of the vertebral spine muscle was highest in the close-up phase. In addition, all of the measured left and right lower limb muscles showed the highest muscle activity between the assisted devices. As a result, We found out that regardless of the method of spike serve and spike, the lower limbs in the run-up phase for a high jump, the vertebrae in the take off phase, the preparation phase for hitting the ball strongly, and in the impact phase at the moment of hitting the ball. It can be seen that it exerts the greatest power in the rectus abdominis.